Alzheimer's Disease-Associated Cerebrospinal Fluid (CSF) Biomarkers do not Correlate with CSF Volumes or CSF Production Rate. - Edsbagge, Mikael; Andreasson, Ulf; Ambarki, Khalid; Wikkelsø, Carsten; Eklund, Anders; Blennow, Kaj; Zetterberg, Henrik; Tullberg, Mats (J Alzheimers Dis, 2017)
BACKGROUND: Neuropathologically, Alzheimer's disease (AD) is characterized by accumulation of a 42 amino acid peptide called amyloid-β (Aβ42) in extracellular senile plaques together with intraneuronal inclusions of hyperphosphorylated tau protein in neurofibrillary tangles and neuronal degeneration. These changes are reflected in the cerebrospinal fluid (CSF), the volumes and production rates of which vary considerably between individuals, by reduced concentration of Aβ42, increased concentration of phosphorylated tau (P-tau) protein, and increased concentration of total tau (T-tau) protein, respectively. OBJECTIVE: To examine the outstanding question if CSF concentrations of AD associated biomarkers are influenced by variations in CSF volumes, CSF production rate, and intracranial pressure in healthy individuals. METHODS: CSF concentrations of Aβ42, P-tau, and T-tau, as well as a number of other AD-related CSF biomarkers were analyzed together with intracranial subarachnoid, ventricular, and spinal CSF volumes, as assessed by magnetic resonance imaging volumetric measurements, and CSF production rate in 19 cognitively normal healthy subjects (mean age 70.6, SD 3.6 years). RESULTS: Negative correlations were seen between the concentrations of three CSF biomarkers (albumin ratio, Aβ38, and Aβ40), and ventricular CSF volume, but apart from this finding, no significant correlations were observed. CONCLUSION: These results speak against inter-individual variations in CSF volume and production rate as important confounds in the AD biomarker research field.